What's missing from the capital gains debate? Real estate and capital gains taxation - Michael Hudson; Kris Feder (Levy Economics Institute of Bard College, 1997)
The recent enactment of a capital gains tax cut resulted, according to the authors, from the absence of a true appreciation or consideration of the real beneficiaries of such a cut, its probable actual effects, the distinction between productive and nonproductive sources of capital gains (two-thirds of capital gains accrue to real estate, which is a fixed, nonproductive asset), and distortions in our current income accounting system (which shield most real estate income from taxation). The across-the-board cut, which treats real estate appreciation and true capital gains as the same, is a giveaway to real estate and will steer capital and entrepreneurial resources to a search for unearned income.
Keywords: 330